Urban Studies in Lithuania: What They Display and Conceal about Vilnius - Tadas Šarūnas (Sociologija: Mintis ir Veiksmas, 2019)
This article analyses the dominant discourses about cities in Lithuanian urban studies. Approaching urban processes in a different way, I suggest to study cities as a dense cluster of dwellings and consider housing as the main field (the Bourdieu’s concept) that structures the material forms of the city. In the first two sections of the article I consider the case of Vilnius and criticize the dominant natural and geopolitical categories and metaphors as limiting our understanding about urban processes. In the third part I argue how a historical genealogy of the symbolic forms of the city might reveal spatial manifestations and practices of power relations. Supplementing the genealogy of the symbolic forms with the analysis of social structures, it is possible to suggest a more relevant approach to study Lithuanian cities. Also, such an approach might facilitate productive cooperation between urban researchers working with different epistemological traditions.